Attraction Sound in the Swiftlets House - Siti Nurzalikha Zaini, Husni Zaini; Kamarul Hawari, Ghazali; Saiful Nizam, Tajuddin (Institutue of Research Engineers and Doctors, 2014)
This research about the analysis of attraction sound for swiftlets to enter the swiftlets house. There are important thing for industry to attract swiftlets enter and build their nests in man-made house. Swiftlet house usually house fitted bird-call recording from original sound in the cave to attract attention bird go inside house to be doing nest. Therefore, this study analyze sound features that has attracted attention bird. Ten samples of swiftlets sound were analyzed by using Fast Fourier Transform in Matlab software to identify sound characteristic that attract swiftlets. Specific sound characteristic for swiftlets attraction on frequency and magnitude of original sound and noise have been identified.